Using the Azo Coupling of 3-Chloro-2-Ethoxiethilaniline for Its Determination in Form of Related Triazene Derivative by Method of the High Performance Liquid Chromatography - Maga, Ivan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Triazene 3-chloro2-ethoxiethilaniline (CEA) from 4-nitrophenyldiazonium cations was synthesized. By elemental analysis method, its structure has been confirmed. The effect of hydrogen ions on the formation of CEA azoderivate was studied within the range of 2.8–12.6 pH, the optimum being pH 3.5–5.5. The decrease in the yield of triazene CEA at pH <3 is due to the dominance of the protonated forms of the output amine, while the decrease at pH >7 is due to a decrease in the diazonium-cation concentration. The yield of amine triazene also depends on the reaction time, as well as on the excess of the diazo reagent. The effect of the concentration of the reagent on the formation of azoderivate was studied, while the diazonium-cation concentration was varied from 1 to 30 times with respect to the amount of CEA. Azoderate is formed already at the ratio of components 1 : 1 in the amount of almost 50% of the theoretically calculated yield of the substance. With a further increase in the concentration of the diazo reagent by up to an order, the amount of formation of azoderivate sharply increases. At concentrations of more than 10 multiple amounts, almost complete formation of azo condensation is achieved. In further studies, its 20 times excess was used. To extract and recover the azoderivate, a number of organic solvents were examined: hexane, toluene, o-xylene, dichloromethane, chloroform, dichloroethane, ethyl acetate, butyl acetate, isoamyl acetate. The best were dichloromethane and chloroform. For practical purposes, chloroform was subsequently used. The kinetics of the formation of azoderivate was studied. Already in the first minutes of the solution exposure, almost half of the theoretically calculated yield of triazene is formed and increases significantly over a period of up to 40 minutes exposure of solutions. With an increase in the interaction time of the components to 40–100 min, the yield of azoderevate increases insignificantly. Optimum is 60 minutes exposure of solutions. A linear dependence of the area of chromatographic peaks on the concentration of CEA is observed in the range 22–4,300 μg/dm3. Based on the data obtained, a methodology for determining CEA in wastewater and soils has been developed.